NOTES ON MEXICAN DRUGS II CHARACTERISTICS AND COMPOSITION OF THE FATTY OIL FROM GUSANOS DE MAGUEY CATERPILLARS OF ACENTROCNEME HESAN LUIS POTOSIERIARIS - BACHSTEZ, MARCELO; ARAGON, ALTAGRACIA (Universidad Nacional Autónoma de Mexico, CD MEXICO, DF, MEX, 1979)
The authors succeeded in infecting the larvae of Triatoma carrioni in the Province of Azuay, Ecuador, with Trypanosoma cruzi There have been several acute and chronic cases of palpable edema in humans in this locality and physicians have long suspected t
NATUR
Keywords: NOTES, MEXICAN DRUGS II, CHARACTERISTICS, COMPOSITION, FATTY OIL, GUSANOS DE MAGUEY CATERPILLARS OF ACENTROCNEME HESPERIARIS; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; ZOOLOGIA GENERAL